Chemistry education student response toward general biology course: A descriptive study - Marneli, Diyyan; Husni, Lailatul (University of Muhammadiyah Malang, 2018)
Chemistry and biology are interrelated branches of science, but students majoring in Chemistry Education are often considered as less ability to understand several biological concepts. The aim of this study was to obtain the information about the response of Chemistry Education students on General Biology course. The research was a descriptive study conducted in August to December 2017 in which the subjects were twenty-four first-semester students of Chemistry Education who take General Biology course at Faculty of Tarbiyah and Teaching Sciences, State Islamic Institute Batusangkar, West Sumatera. The instrument used was the questionnaire of student responses on General Biology course. The analysis used was descriptive statistical analysis by using percentage.Â The best response of students on General Biology course is on assessment transparency aspect, while the lowest response is on lecture attractiveness aspect. The conclusion, the response of Chemistry Education student who has taken General Biology course in State Islamic Institute Batusangkar on the criteria good. Although from Chemistry Education Program, most students give positive responses to General Biology course. Information obtained from this study can be used as a basis for improving the quality of General Biology course, especially in Chemistry Education Program.